Self-reported healthcare utilization by adults with diabetic retinopathy in the United States. (2nd November 2018) - Willis, Jeffrey R.; Doan, Quan V.; Gleeson, Michelle; Haskova, Zdenka; Ramulu, Pradeep; Morse, Lawrence; Cantrell, Ronald A.
ABSTRACT: Purpose: To assess healthcare utilization patterns across diabetic retinopathy (DR) severity levels in the United States (US). Design: Cross-sectional study of 699 adults, participating in the 2005–2008 National Health and Nutritional Examination Surveys. Methods: Diagnosis of DR was based on fundus photographs and categorized as: (1) no DR; (2) mild/moderate nonproliferative DR (NPDR); and (3) severe NPDR/proliferative DR (PDR). Healthcare utilization patterns were assessed during a household questionnaire where survey participants self-reported: (1) awareness that diabetes had affected their eyes; (2) pupil-dilation during the past year; and (3) visits to a diabetes education/nutrition specialist during the past year. Results: Among adults with self-reported diabetes, the proportion of those that were aware that diabetes had affected their eye was 15.3% [95% confidence interval (C.I.)] 10.9–19.6%), 21.7% (95% C.I. 14.6–28.7%), and 81.5% (95% C.I. 66.5–96.5%) across those with no retinopathy, mild/moderate NPDR, and severe NPDR/PDR, respectively (p < 0.01). The utilization of a diabetic education/nutrition specialist during the past year was 30.4% (95% C.I. 24.8–36.0%), 31.8% (95% C.I 23.4–40.2%), and 55.9% (95% C.I. 32.3–79.6%) across those with no retinopathy, mild/moderate NPDR, and severe NPDR/PDR, respectively (p = 0.13). Pupil dilation within the past year was 62.2% (95% C.I. 56.3–68.1%), 62.1% (95% C.I. 53.4–70.8%), and 93.8% (95% C.I. 87.3–100.0%) across those with no DR, mild/moderate NPDR, and severe NPDR/PDR, respectively (p = 0.01). Conclusions: Adults with diabetes in the United States, even those with the most severe forms of DR, do not fully utilize healthcare services for diabetic eye disease. Future studies should aim to address barriers to appropriate diabetes care.